Vous êtes sur la page 1sur 6

hw9-10.

nb: 9/24/04::9:04:50

Homework: Due 9-10-04


Sakurai Chap 1: 1,4,8,10
1.1
There are probably lots of clever answers that are successive applications of variations of
#AB, C' = A#B, C' + #A, C' B = A B, C - A, C B

but in this case straight brute force is easiest. On the left

#AB, CD' = ABCD - CDAB


while on the right

-ACD, B + A C, B D - C D, A B + C, A DB =


= -ACDB - ACBD + ACBD + ABCD - CDAB - C ADB + C ADB + ACDB
= -ACDB + ABCD - CDAB + ACDB
= ABCD - CDAB
which checks.
1.4

a) tr+X Y / = i ;i X Y i?
= ij ;i X j? ; j Y i?
= ij ; j Y i? ;i X j?

= j ; j Y X j? = tr+Y X /

note in line 3 the matrix elements are just c-numbers and, so, commute.
b) Consider the action of +X Y / between two arbitrary states
;a +X Y / b? = ;b X Y a?*
= +i ;b X i? ;i Y a?/*
= i ;i X b? ;a Y i?
= i ;a Y i? ;i X b?
= ;a Y X b?

c) Let ;x', ;x be arbitrary states, and i? be eigenstates of A

hw9-10.nb: 9/24/04::9:04:50

;x' ei f A x? = i j ;x' i? ;i ei f A j? ; j x?
= i j ;x' i? ;i ei f a j j? ; j x?
= i j ;x' i? ei f a j di j ; j x?
= j ;x' j? ei f a j ; j x?
so

ei f

= ei f a j j ? ; j
j

d) a ya * +x/ ya +x'/ = a ;a x? ;x' a? = a ;x' a? ;a x? = ;x' x? = d+x - x'/


1.8
I'll give one example in gory detail bra-ket notation, repeat that example in matrix notation, and then confirm the
remaining results in matrix notation.
Given Sx = 2 ++? ;- + -? ;+/, S y = i 2 +- +? ;- + -? ;+/, and Sz = 2 ++? ;+ - -? ;-/; show
#Si , S j ' = iei jk Sk . For the case #Sx , S y ' = iSz , start with

Sx S y = i
4 ++@ ;- + -@ ;+0 +- +? ;- + -@ ;+0
2

LM - +? ;- +? ;-
MM
MM + +? ;- -? ;+
2 M
= i 4 MM
MM - -? ;+ +? ;-
MM
N + -? ;+ -? ;+

=
0
\]
]
= + +? ;+ ]]]
2

]] = i
]
4 ++@ ;+ - -@ ;-0 = i
2 Sz
= - -? ;- ]]
]]
=
0
^

Similarly, reversing the order



S y Sx = i
4 +- +? ;- + -@ ;+0 ++@ ;- + -@ ;+0
2

LM - +? ;- +? ;-
MM
M - +? ;- -? ;+
2 M
= i
4 MMM
MM + -? ;+ +? ;-
MM
N + -? ;+ -? ;+

=
0
\]
]
= - +? ;+ ]]]
2
]] = i
+- +? ;+ + -@ ;-0 = -i 2 Sz
4
= + -? ;- ]]]
]]
=
0
^

Combining the two results, #Sx , S y ' = Sx S y - S y Sx = iSz . This same result is much more compact if done in a matrix
L 0 1 \]
L 0 -1 \]
L 1 0 \]
notation where Sx = 2 MM
], S y = i 2 MM
], and Sz = 2 MM
]. Then
N1 0^
N1 0 ^
N 0 -1 ^

#Sx , S y ' = Sx S y - S y Sx =

1 0 \
L 0 1 \] LM 0 -1 \] LM 0 -1 \] LM 0 1 \]\]
L 1 0 \] LM -1 0 \]\]
2 L
2 L
2 L
]] = iSz
i
4 MMMM
4 MMMM
2 MM
]M
]-M
]M
]] = i
]-M
]] = i
NN 1 0 ^ N 1 0 ^ N 1 0 ^ N 1 0 ^^
NN 0 -1 ^ N 0 1 ^^
N 0 -1 ^

Similarly, it is straightforward to show #Sx , Sz ' = -iS y and #S y , Sz ' = iSx . Combining the three results,
#Si , S j ' = iei jk Sk .
To confirm the first of the "off-diagonal" anti-commutator relations

0 1 \ L 0 -1 \ L 0 -1 \ L 0 1 \\
2 L
MLM
]M
]] + MM
]] MM
]]]] = 0
Sx , S y  = Sx S y + S y Sx  = i
4 MM 1 0 ] M 1
0 ^ N 1 0 ^ N 1 0 ^^
NN
^N

hw9-10.nb: 9/24/04::9:04:50

and

0 1 \ L 0 1 \ 2 L 1 0 \ 2
2 L
M
]M
]
M
]
Sx , Sx  = Sx Sx + Sx Sx  = 2 Sx Sx =
2 M 1 0 ] M 1 0 ] =
2 M 0 1 ] =
2 I
N
N
^N
^
^


di j
Combining these results with others for S y and Sz , the more general result follows, Si , S j  =
2

1.10
I did this by hand, but there are tools for this sort of thing...Here is H
h  a, a, a, a;
MatrixFormh


a a

a a

This solves for the eigenvalues and eigenvectors


evals, evectors  Eigensystemh;
evals
MatrixForm  evectors

 2 a, 2 a
1 

2


1



,



1 2


1






Test result
MatrixFormSimplifyh.# &  evectors


 2 2  a 






,

 2 a




2 2  a 









2 a



The eigenstates aren't normalized, so


norms  SimplifySqrt#.# &  evectors



 4  2 2 , 
2 2 2 

hw9-10.nb: 9/24/04::9:04:50

normvectors  Simplifyevectors  norms


MatrixForm  normvectors

1 2
1
1 2
1
 
 , 
 ,  
 , 







2 2 2 
2 2 2 
42 2
42 2
1 2









42 2





1

 


42 2








,






1 2






  



2 2 2  










1




 




2
2
2





Not that pretty.

Bransden and Joachain 5.7, 5.11


5.7

a) Show i) #xn , p' = inxn-1 and ii) #x, pn ' = in pn-1

i) Use induction. Assume that #xn , p' = inxn-1 is true for n, then show that it is also true for n + 1. Specifically,
#xn+1 , p' = #xxn , p'
= x#xn , p' + #x, p' xn
= xinxn-1 + ixn
= i+n + 1/xn

where in the third line we used the assumed result and that #x, p' = i. This last relation also shows that the hypothesis
is true for n = 1. It follows that it is true for all n 1.

ii) Similarly

#x, pn+1 ' = #x, p pn '


= p#x, pn ' + #x, p' pn
= pin pn-1 + i pn
= i+n + 1/ pn

which shows the inductive part, and #x, p' = i establishes the result for n = 1.
b i) Using a power series expansion for f ,

# f +x/, p' = %S fn xn , p)
= S fn #xn , p'
n

= S fn inxn-1
n

n
= i
x S fn x

f +x/

= i

b ii) A similar power series substitution yields

hw9-10.nb: 9/24/04::9:04:50

#x, g+p/' = %x, S gn pn )


n

= S gn in pn-1
n

= i
p g+p/

5.11
Consider

LM 1 0 0 \]
LM 0 1 0 \]
LM 2 0 0 \]
MM
]]
MM
]]
M
]
H = wMMM 0 2 0 ]]] , A = lMMM 1 0 0 ]]] , and B = mMMMM 0 0 1 ]]]]
M
]
M
]
M
]
N0 0 2^
N0 0 2^
N0 1 0^

a) The eigenvalues and normalized eigenvectors of A are, l,


H
2

LM 1 \]
MM ]]
1
MM 1 ]]!, -l,

H
MM ]]
2
N0^

LM 1 \]
MM
]
MM -1 ]]]!, 2 l,
MM
]]
N 0 ^

LM 0 \]
MM ]]
MM 0 ]]!.
MM ]]
N1^

LM 0 \]
LM 0 \]
LM 1 \]
MM ]]
MM
]]
M ]
1
MM 1 ]]!, -m,
 MMM 1 ]]]!, 2 m, MMMM 0 ]]]]!. Note that for both A and B, I've adopted a common phase
And for B, m,
H
MM ]]
2 M
]
M ]
N1^
N -1 ^
N0^
convention that the first non-zero component in the eigenvector is chosen to be real and positive.
1


H
2

LM 1 \]
LM 0 \]
LM 0 \]
MM ]]
MM ]]
M ]
The eigenvalues Ei and eignvectors ui ? for H are, w, MMM 0 ]]]!, 2 w, MMM 1 ]]]!, 2 w, MMMM 0 ]]]]!. Note that the eigenvalue
M ]
M ]
M ]
N0^
N0^
N1^
E = 2 w is doubly degenerate. An arbitrary state u? can be written as a linear combination of energy eigenstates,

u? = c1 u1 ? + c2 u2 ? + c3 u3 ?

b i) If u? is normalized to unity
1 = ;u u? = +c1* ;u1 + c2* ;u2 + c*3 ;u3 / +c1 u1 ? + c2 u2 ? + c3 u3 ?/ = c1 2 + c2 2 + c3 2 = S ci 2 = 1
i

ii) The expectation value ;H ?u = ;u H u? = w+c1 2 + 2 c2 2 + 2 c3 2 /. For ;A? and ;B? a bit more algebra is required.

;A? = l+

c*1

c*2

c*3

;B? = m+

c*1

c*2

c*3

LM 0 1 0 \] LM c1 \]
M
]M ]
/ MMMM 1 0 0 ]]]] MMMM c2 ]]]] = l+c1 c*2 + c2 c*1 + 2 c3 2 /
M
]M ]
N 0 0 2 ^ N c3 ^

LM 2 0 0 \] LM c1 \]
M
]M ]
/ MMMM 0 0 1 ]]]] MMMM c2 ]]]] = m+c3 c*2 + c2 c*3 + 2 c1 2 /
M
]M ]
N 0 1 0 ^ N c3 ^

iii) Possible measurements of the energy are the eigenvalues of H , w and 2 w. After a measurement of the energy, the
system will be in an eigenstate corresponding to the energy eigenvalue, i.e. the system will be projected onto the
subspace corresponding to that eigenvalue. For w, there is a single eigenstate so that after the measurement the state
will be

hw9-10.nb: 9/24/04::9:04:50

u'? = # Pw u?
= # P1 u?
= # u1 ? ;u1 u?
= # u1 ? ;u1 +c1 u1 ? + c2 u2 ? + c3 u3 ?/
= # c1 u1 ?

where # is a normalization constant, and after normalization u'? = u1 ?.

Simlarly, the projection onto the E = 2 w subspace is P2 w = P2 + P3 = u2 ? ;u2 + u3 ? ;u3 and so after a measurement
yielding 2 w
1
u'? = # P2 w u? =
c u ? + c3 u3 ?
Sc W2 +Sc W2 2 2
2